Reconfigurable System with Virtuoso Real-Time Kernel and TEV Environment - Andrade, M. C.; Moron, C. E.; Saito, J. H (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2006)
This paper presents an easy procedure to develop a reconfigurable application in a Virtuoso real-time operating system using the visual environment TEV developed at DC/UFSCar. In TEV, applications are built using graphs, where nodes are data structures that compose a parallel program (tasks, signals, resources, mailboxes, etc.), and arrows denote the communication and synchronization operations between the data structures. The information in the graphical model can be complemented with code written by the user. Based on this construction, the source code of the application is automatically generated. This work describes a proposal of the TEV extension with reconfigurable applications, denoting R-TEV, using a reconfigurable functions library. A case study is presented, using three reconfigurable functions, and the results show that the proposal is feasible.